Increasing the antimicrobial activity of Pseudomonas brassicacearum S-1 by inactivation of lysR3 and mtfA genes - Muratova, Anna A.; Mandryk-Litvinkovich, Maryna N.; Valentovich, Leonid N. (Experimental Biology and Biotechnology, 2021)
Site-specific markerless inactivation of genes lysR3 and mtfA of bacteria Pseudomonas brassicacearum S-1 was carried out. It was shown that strains P. brassicacearum S-1-lysR3, P. brassicacearum S-1-mtfA and P. brassicacearum S-1-lysR3-mtfA demonstrate increased antagonistic activity against a number of phytopathogens 1.2–1.6 times higher compared with the original strain. In the laboratory experiment, mutant variants did not affect growth and development of tomato, cucumber and parsley plants. Treating tomato and cucumber seeds with a solution of the culture of the strain P. brassicacearum S-1-lysR3-mtfA led to the increase of seedlings roots length by 1.4 times compared with the original strain. We also determined that the examined strains were able to survive in the soil microbial consortium.
Keywords: mutagenesis; recombineering; antimicrobial activity; Pseudomonas brassicacearum; growth stimulation